Characteristics of patients with incidental eosinophilia admitted to a tertiary hospital in southern China - Bigui Chen; Qiuping Rong; Yu Fu; Hanwen Liang; Xuetao Kong; Qingling Zhang; Mei Jiang; Zhufeng Wang; Jiaxing Xie (Heliyon, 2023)
Background: The characteristics of patients with eosinophilia are heterogeneous and the outcomes can vary from asymptomatic to severe. Objective: To describe the feature of patients with eosinophilia in a single center. Design: Based on the electronic medical records from Yangjiang People's Hospital in China, the inpatients admitted between June 2018 and February 2021 with measured blood eosinophil counts were evaluated. Methods: Eosinophilia was defined as a peripheral blood eosinophil count of ≥0.5 × 109/L. Differences were compared by eosinophilia severity. The medical records of patients with moderate to severe eosinophilia were reviewed and summarized in terms of examination, diagnoses and management. And these patients were matched with patients without incidental eosinophilia by propensity score and the differences were compared. Results: A total of 7,835 patients with eosinophilia were identified out of 131,566 total inpatients. All types of eosinophilia were most common in males (8.2%; 5,351/65,615), and in patients aged 0–6 years (11.6%; 1,760/15,204), and in the pediatric (10.8%; 1,764/16,336) department, followed by dermatology (10.6%; 123/1,162), Oncology (7.5%; 394/5,239) and Intensive care unit (ICU) (7.4%; 119/1,608). Patients with moderate to severe eosinophilia were more likely to admit to ICU (moderate: 1.3%; severe: 0.50%). In patients with moderate to severe eosinophilia, only 205/621 (33%) had eosinophilia mentioned in their records, and only 63/621 (10.1%) underwent investigations for eosinophilia. The majority of patients with moderate to severe eosinophilia (372/621, 59.9%) had an infectious disease, and little examination (7.4%; 46/621) was taken to identify the cause of eosinophilia, and only 39/621 (6.3%) of patients had a discrete cause of eosinophilia identified. Patients with moderate to severe eosinophilia (24.3%; 151/621) exhibited certain chance to have organ dysfunction. Conclusion: Incidental eosinophilia in inpatients was frequently neglected and less investigated. Multidisciplinary consultation may improve outcomes of inpatients with moderate to severe eosinophilia.